The symmetry analysis and optimum conception for thermoelectric converters with non-uniform legs - Korzhuev, M.A.; Baikov, A.A. (Ye.A.Buketov Karaganda State University Publishing house, 2010)
The symmetry analysis was applied to the thermoelectric converters of energy (generators (TEG), coolers (TEC), and heaters (TEH)) with non-uniform legs (inhomogeneous, segmented, graded, functionally graded, and of non- regular shape). The concept of symmetry was used in a widen sense that includes space order and proportion, harmony, synergism, and also all their infringements in modules. The analysis was carried out within four structural levels including ones for the materials, the legs, the thermocouples, and the group of converters of energy. The increase in Z for the converters with non-uniform legs was shown to be due to the additional contributions of “bulk” thermoelectric effects in a combination with the decrease of the contribution of irreversible processes (Joule's heat emission and heat conductivity) at the breakdown of the symmetry of the legs. The crystallographic symmetry of thermoelectric materials and the own symmetry of the legs and modules providing the increase of the figure of merit Z for converters was specified. For the group of converters with non-uniform legs the modified tetratomic classification (TEGa, TEGb, TEC, and TEH) was proposed. The general rule for the proper set of the legs in thermoelectric converters was developed. Some new effects observed in inhomogeneous legs and on their borders as well as the practical application of inhomogeneous legs for cooling, domestic heating, waste heat utilization and power generation were discussed (Grant of Russian Basic Research Foundation № 06-08-00084).
Keywords: thermoelectric converters; thermocouples; thermoelectric effects; crystallographic symmetry